2016
DOI: 10.1589/jpts.28.207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluatıng the effectiveness of frozen shoulder treatment on the right and left sides

Abstract: [Purpose] To evaluate treatments with interferential current, hot pack, ultrasound therapy, stretching, strengthening and range-of-motion exercises, comparing between the right and left shoulders in terms of pain and functional capacity in patients with frozen shoulder. This was a retrospective study. [Subjects and Methods] Sixty-four patients (34 right side, 30 left side) were treated with interferential current and hot pack application for 20 min each, ultrasound therapy for 3 min, regular range-of-motion ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Similarly, Nazligul et al [28] recently concluded that IFT does not provide additional effect to a multimodal approach including cryotherapy, exercise, and non-steroidal anti-inflammatory drugs for patients with SAPS. On the contrary, it has been demonstrated that the combination of IFT with shoulder exercises [55], ultrasound, thermotherapy, and stretching [56] is effective in the management of frozen shoulders. Likewise, the use of IFT alone has shown to be clinically effective to relieve pain during movement and to increase pain-free passive shoulder mobility in hemiplegic shoulder pain [57] and, when combined with exercise therapy, seems to improve pain, function, and quality of life in individuals with shoulder impingement syndrome [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Nazligul et al [28] recently concluded that IFT does not provide additional effect to a multimodal approach including cryotherapy, exercise, and non-steroidal anti-inflammatory drugs for patients with SAPS. On the contrary, it has been demonstrated that the combination of IFT with shoulder exercises [55], ultrasound, thermotherapy, and stretching [56] is effective in the management of frozen shoulders. Likewise, the use of IFT alone has shown to be clinically effective to relieve pain during movement and to increase pain-free passive shoulder mobility in hemiplegic shoulder pain [57] and, when combined with exercise therapy, seems to improve pain, function, and quality of life in individuals with shoulder impingement syndrome [58].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the use of electrotherapy may evoke a long sustained placebo-induced pain relief effect [61]. In this sense, most of the previous studies investigating the role of IFT on shoulder pain have not included sham IFT as a control intervention [54,55,56,58]. Third, the clinical context and the social connection between patient and therapist seem to modulate the effect of IFT [62,63], although these aspects have been scarcely controlled in the existing literature.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the report by Ludewig and Cook 23 ) , it was demonstrated that scapular upward rotation was decreased at 60° of humeral elevation in subjects with subacromial impingement. Taking these findings together, it can be suggested that early postoperative passive motion may increase the risk of re-tearing in the repaired cuff as a consequence of reduced scapular support; however, passive motion would be beneficial in cases of adhesive capsulitis because the glenohumeral motion is reduced 29 , 30 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 40% of frozen shoulder patients without proper treatment suffered from persistent pain and limited range of motion, and 11% showed permanent shoulder dysfunction2, 3 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The main symptoms of a frozen shoulder are pain and stiffness in the glenohumeral joint 1 ) . It has been reported that 40% of frozen shoulder patients without proper treatment suffered from persistent pain and limited range of motion, and 11% showed permanent shoulder dysfunction 2 , 3 ) .…”
Section: Introductionmentioning
confidence: 99%